Elicitação de Requisitos para uma plataforma de ensino de Gestão de Projetos de Software - Ricardo Fernando Babo Pedroso (2015)
Software is a broad discipline that encompasses a diverse set of knowledge topics. Teaching software project management can be challenging, as the set of skills that students should acquire is very practical, so the traditional method of teaching may not be the best choice for this specific domain area. Through analysis of currently available learning platforms, none is properly designed to teach, specifically, management of software projects. This paper presents a process of gathering requirements for a software project management teaching platform. The process begins with the identification of stakeholders for this platform and its goals, followed by the analysis of similar systems, a workshop with students, questionnaires and interviews. The results of this paper can be used as a basis to design and develop a teaching platform for software project management.